Development of a neurofeedback-based virtual reality environment - Dias, Jorge Miguel Ribeiro (2018)
Recent technology has continuously expanded the reaching spectre of psychotherapy. In the latest years, the development of digital environments, coupled with the evolution of sensorial hardware, has demonstrated usefulness and effectiveness in some areas of psychotherapy such as phobia treatment and attention deficit hyperactivity disorder management through neurofeedback training. However, the generality of these equipments is very expensive. In this project, an audiovisual stimuli virtual reality environment was developed, capable of displaying signals provided by an electroencephalography-based brain-computer interface. This environment has the objective of providing its user with neurofeedback training and being suited for affordable hardware equipments. Development of the aforementioned environment took place in the Unity3D ® game engine version 5.3.0f4, using C# scripting developed in Microsoft ® Visual Studio 2015 TM. As for the virtual reality display, an Oculus Rift ® development kit 1 was used for testing, together with the Oculus runtime for Windows ®, version 0.8.0.0. The used brain-computer interface was Neurosky’s Mindband TM, a research tool with a single electroencephalography channel, mediated through the ThinkGear Connector, version 3.1.8.0. The creation of this environment as an application directed towards neurofeedback training and compatible with affordable equipments is a contribution towards a reality where virtual reality is more synchronized with our society.